Evaluation of the attenuation, immunogenicity, and efficacy of a live virus vaccine generated by codon-pair bias de-optimization of the 2009 pandemic H1N1 influenza virus, in ferrets. Issue 4 (20th January 2016) - Broadbent, Andrew J.; Santos, Celia P.; Anafu, Amanda; Wimmer, Eckard; Mueller, Steffen; Subbarao, Kanta
Highlights: We generated a 2009 pH1N1 vaccine virus with codon pair bias de-optimized HA & NA genes. The vaccine virus was clinically attenuated and immunogenic in a ferret model. The vaccine virus protected ferrets from challenge with wt 2009 pH1N1 virus. Additional de-optimization is needed to reduce vaccine virus replication in ferrets. Abstract: Codon-pair bias de-optimization (CPBD) of viruses involves re-writing viral genes using statistically underrepresented codon pairs, without any changes to the amino acid sequence or codon usage. Previously, this technology has been used to attenuate the influenza A/Puerto Rico/8/34 (H1N1) virus. The de-optimized virus was immunogenic and protected inbred mice from challenge. In order to assess whether CPBD could be used to produce a live vaccine against a clinically relevant influenza virus, we generated an influenza A/California/07/2009 pandemic H1N1 (2009 pH1N1) virus with de-optimized HA and NA gene segments (2009 pH1N1-(HA + NA) Min ), and evaluated viral replication and protein expression in MDCK cells, and attenuation, immunogenicity, and efficacy in outbred ferrets. The 2009 pH1N1-(HA + NA) Min virus grew to a similar titer as the 2009 pH1N1 wild type ( wt ) virus in MDCK cells (∼10 6  TCID50 /ml), despite reduced HA and NA protein expression on western blot. In ferrets, intranasal inoculation of 2009 pH1N1-(HA + NA) Min virus at doses ranging from 10 3 to 10 5 TCID50 led to seroconversion in all animals and protection from challenge with the 2009 pH1N1 wt virus 28 days later. The 2009 pH1N1-(HA + NA) Min virus did not cause clinical illness in ferrets, but replicated to a similar titer as the wt virus in the upper and lower respiratory tract, suggesting that de-optimization of additional gene segments may be warranted for improved attenuation. Taken together, our data demonstrate the potential of using CPBD technology for the development of a live influenza virus vaccine if the level of attenuation is optimized.